STRATEGI PENINGKATAN KINERJA SUMBER DAYA MANUSIA PADA PERUSAHAAN KONSTRUKSI PT. JAYA KUSUMA SARANA BALI MELALUI PENDEKATAN BUDAYA ORGANISASI - Ni Made Sintya Rani; GAP. Candra Dharmayanti; I B. Rai Adnyana (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2016)
Abstract : One of the key success factors of a contractor company in achieving their vision and mission is good quality of human resources (HR). Based on ISO 9001 evaluation, the quality of HR at PT. Jaya Kusuma Sarana Bali (PT.JKS Bali) that measured by indicators of objectives and targets from each division concluded that the quality of HR still need to be improved. By knowing the profile of the current and preferred organizational culture, it can be identified the strategy required to achieve the vision and mission of the organization. This study aimed to analyze the culture profile of PT. JKS Bali based on their employees perception, in order to identify strategies for improving their HR performance. The method used is an OCAI (Organizational Culture Assessment Instrument) analysis method and a survey using the OCAI questionnaire. The analysis involved identification of the culture profiles that measured in 6 key dimensions (i.e.: Dominant Characteristics, Organizational Leadership, Management of Employees, Organization Glue, Strategic Emphases and Criteria of Success) which can represent the four culture types of an organization (i.e.: Clan, Adhocracy, Market dan Hierarchy). The result suggests that the profile of the current and preferred organizational culture at PT.JKS Bali does not require significant changes. The strategies that need to be implemented derived from six key dimensions, Applying more flexible organizational leadership but also against the rules, Managing the employees who prioritize teamwork, Reducing formalities working procedures, focusing on the company's internal, emphasizing human resource development and employment commitments.